ANALISIS KOMPARATIF KUALITAS PRODUK DAN DAYA SAING USAHA MIKRO, KECIL, DAN MENENGAH: STUDI KASUS KOTA BATU, JAWA TIMUR DAN KOTA PALU, SULAWESI TENGAH - Rendy Kurniawan; Anang Ma’ruf; Yorensia Resti; Siti Nurfadila; Novita Sari; Nadia I Tala’a; Miftah Amalia; Mastang Mastang; Nuraisyah Nuraisyah; Andi Maman; Fachrul Reza (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This study aims to analyze and compare the product quality and competitiveness of Micro, Small, and Medium Enterprises (MSMEs) in Batu City, East Java, and Palu City, Central Sulawesi. The research method used is a qualitative approach with data collection techniques through documentation studies, observations, and in-depth interviews with MSME actors, stakeholders, and relevant agencies in both regions. The results show that MSMEs in Batu City have advantages in terms of marketing access, tourism infrastructure support, and more established cross-sector collaboration. In contrast, MSMEs in Palu City demonstrate resilience in local product innovation and the potential for post-disaster tourism-based development. Both regions face similar challenges in terms of access to capital, digital technology adoption, and improving the quality of human resources. This study recommends the importance of strengthening the MSME ecosystem through improving product quality, expanding digital market access, and strategic collaboration between the government, business actors, and academics to increase MSME competitiveness at the national and global levels.